The development of burn scar contractures and impact on joint function, disability and quality of life in low- and middle-income countries: A prospective cohort study with one-year follow-up. Issue 1 (February 2022) - Hendriks, T.C.C.; Botman, M.; Binnerts, J.J.; Mtui, G.S.; Nuwass, E.Q.; Niemeijer, A.S.; Mullender, M.G.; Winters, H.A.H.; Nieuwenhuis, M.K.; van Zuijlen, P.P.M.
Highlights: In a low-income country the prevalence of burn scar contractures was high at one year post-injury. From discharge up to one year post-injury half of the joint contractures resolved to normal flexibility. Joints that developed a contracture over time were limited in performing daily activities. Predictors for developing contractures were prolonged patient delay and large, deep burns. Patients who developed burn scar contractures reported more disability and lower quality of life. To limit the development of contractures, timely access to safe burn care should be improved in low-income countries. Abstract: Objective: The aim of this study was to assess the development of burn scar contractures and their impact on joint function, disability and quality of life in a low-income country. Methods: Patients with severe burns were eligible. Passive range of motion (ROM) was assessed using lateral goniometry. To assess the development of contractures, the measured ROM was compared to the normal ROM. To determine joint function, the normal ROM was compared to the functional ROM. In addition, disability and quality of life (QoL) were assessed. Assessments were from admission up to 12 months after injury. Results: Thirty-six patients were enrolled, with a total of 124 affected joints. The follow-up rate was 83%. Limited ROM compared to normal ROM values was observed in 26/104 joints (25%) at 12 months. Limited functional ROM was observed in 55/115 joints (48%) at discharge and decreased to 22/98 joints (22%) at 12 months. Patients who had a contracture at 12 months reported more disability and lower QoL, compared to patients without a contracture (median disability 0.28 versus 0.17 ( p = 0.01); QoL median 0.60 versus 0.76 ( p = 0.001)). Significant predictors of developing joint contractures were patient delay and the percentage of TBSA deep burns. Conclusion: The prevalence of burn scar contractures was high in a low-income country. The joints with burn scar contracture were frequently limited in function. Patients who developed a contracture reported significantly more disability and lower QoL. To limit the development of burn scar contractures, timely access to safe burn care should be improved in low-income countries.